Non-Metallic Mineral and Rock Mining Policy Within Metallic Mineral Concession Areas: Analysis and Strategic Recommendations - Jumbadi, Jumbadi (CV. Publikasi Indonesia, 2025)
Indonesia's position as the world's largest nickel producer, holding 42% of global reserves, has intensified mining activities across Sulawesi. However, recent findings by the Audit Board (BPK) in 2024 revealed systemic exploitation of regulatory loopholes, where non-metallic mineral permits (IUP) for rocks like peridotite and limestone are being misused to extract high-value nickel in Central and Southeast Sulawesi. This practice stems from three critical factors: (1) significantly easier permitting processes for rock commodities (14-day approval) versus metallic minerals (22-day auction system), (2) inadequate verification mechanisms for mineral content in rock concessions, and (3) weak coordination between central and regional oversight bodies. This study examines the multidimensional impacts of such permit misuse through qualitative policy analysis, incorporating geological assessments of nickel-bearing rock formations, comparative evaluation of licensing procedures, and economic modeling of state revenue losses. Findings demonstrate that 5%-10% unauthorized nickel extraction under rock permits could incur state losses of IDR 22.8-45.5 trillion annually, while simultaneously causing environmental degradation and undermining legitimate mining operations. The research proposes tiered policy interventions including real-time monitoring through the MOMI/MODI systems, mandatory nickel content verification for rock permits, and revised commodity classification frameworks. These recommendations aim to reconcile Indonesia's mineral governance with its dual objectives of resource nationalism and sustainable development, particularly crucial as the nation advances its nickel down streaming agenda.